Japan and China in East Asian Integration - Lim, Hua Sing (Book collections on Project MUSE., 2008)
"This is an excellent and versatile textbook, as well as an intervention in the scholarly debate on the Asian economies. During the last few years Lim has paid particular attention to China, realizing that the Chinese and Japanese economies are complementary and dependent on each other. The chapters are free-standing, which makes it easier to use the book as a text, as the instructor can be selective, if needed."--Professor Hans C. Blomqvist, Swedish School of Economics and Business Administration, Helsinki, Finland "Professor Lim's book is not only a discussion of the Japanese